The attitude of future teachers in the field of physical education to education as a key professional task - Ponomarev G.N.; Radionova N.F.; Rivkina S.V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the main characteristics of the attitude of future teachers in the field of physical education to education as a professional task of pedagogical activity and to determine ways to improve their professional training for organizing the education of the younger generation. The study was based on the concept of «Competency-based approach in teacher education» [1, 7]. Results and conclusions. Based on the analysis, generalization and systematization of the obtained research data, the article presents the characteristics of the attitude of future teachers in the field of physical education to education as a professional task of pedagogical activity. These characteristics are revealed through a number of indicators: the importance of education for future teachers; priorities of students in educational tasks, the most important in modern conditions and the most difficult to solve; priorities of students in educational methods that are the most productive in modern conditions and most often used in educational practice; priorities of students in the forms of educational work that are the most productive in modern conditions and most often used in educational practice.